Bone union‐promoting effect of romosozumab in a rat posterolateral lumbar fusion model. Issue 11 (4th February 2022) - Kim, Geundong; Inage, Kazuhide; Shiga, Yasuhiro; Mukaihata, Tomohito; Tajiri, Ikuko; Eguchi, Yawara; Suzuki‐Narita, Miyako; Takaoka, Hiromitsu; Hozumi, Takashi; Mizuki, Norichika; Tsuchiya, Ryuto; Otagiri, Takuma; et al.
Abstract: This study investigated the effect of romosozumab on bone union in a rat posterolateral lumbar fixation model. Posterolateral lumbar fixation was performed on 8‐week‐old male Sprague Dawley rats ( n = 20). For bone grafting, autogenous bone (40 mg) was harvested from the spinous processes of the 10th thoracic vertebra until the 2nd lumbar vertebra and implanted between the intervertebral joints and transverse processes of the 4th and 5th lumbar vertebrae on both sides. Rats were matched by body weight and equally divided into two groups: R group (Evenity®, 25 mg/kg) and control (C) group (saline). Subcutaneous injections were administered twice a week until 8 weeks after surgery. Computed tomography was performed at surgery and week 8 after surgery. The area and percentage of bone trabeculae in the total area of bone fusion were calculated. Statistical analysis was performed using an unpaired t test ( p < 0.05). We found that the R group rats had significantly higher mean bone union rate and volume than did the C group rats at all time courses starting week 4 after surgery. The R group had significantly higher increase rates than did the C group at weeks 4 and 6 after surgery. The percentage of bone trabeculae area in the R group was approximately 1.7 times larger than that in the C group. Thus, we demonstrated that romosozumab administration has stimulatory effects on bony outgrowth at bone graft sites. We attribute this to the modeling effect of romosozumab.